2005
DOI: 10.1021/jo0508705
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly with Degenerate Prototropy

Abstract: This work describes a rational approach for addressing the prototropy-related problems in heterocycle-based self-assembling systems by the use of degenerate prototropy. As a proof of principle, the utility of degenerate prototropy is demonstrated herein by developing heterocycle-based AADD-type self-assembling modules that exist as "single set of protameric pair (duplex)" in both solution and solid states. These self-assembling modules are quickly accessible in good yield by reacting 2-amino-5,5-disubstituted-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…[12] However,when the protic solvent ethanol (C 2 D 5 OD) is introduced, the intensity as well as the position of these NH signals changes signifi-cantly.T hese low-field NH proton signals completely disappear when the volume ratio of [D 6 ]ethanol is 20 %o rm ore (Figure 2b,c), implying that the intermolecular hydrogen bonds have been largely disassembled. [14] This was supported by the 1 HNMR and X-ray diffraction data. [12,13] However,t he ADAD tautomer and ADAD-DADAd imeric structure are effectively inhibited by the degenerate prototropy effect in the modified molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[12] However,when the protic solvent ethanol (C 2 D 5 OD) is introduced, the intensity as well as the position of these NH signals changes signifi-cantly.T hese low-field NH proton signals completely disappear when the volume ratio of [D 6 ]ethanol is 20 %o rm ore (Figure 2b,c), implying that the intermolecular hydrogen bonds have been largely disassembled. [14] This was supported by the 1 HNMR and X-ray diffraction data. [12,13] However,t he ADAD tautomer and ADAD-DADAd imeric structure are effectively inhibited by the degenerate prototropy effect in the modified molecule.…”
Section: Introductionmentioning
confidence: 99%
“…12,18 Symmetrically substituted 5,5-dialkyl-4,6dioxo-1,4,5,6-tetrahydro-pyrimidin-2-yl-urea derivatives have finally resolved the problem of nondegenerate tautomerism (Chart 1). 19 Ureido-s-triazine-bridged assemblies of various oligo(phenylenevinylene) donors and the perylene bisimide acceptor 20 and noncovalently bonded dimers of amidinium-substituted metalloporphyrins 21 or tetrathiofulvalenes 22 and a fullerenesubstituted benzoate provide intriguing examples of efficient photochemically triggered electron transfer from the excited donor to the acceptor across strong hydrogen bridges. Directed energy transfer in these systems profits from the thermodynamic driving force imminent in the relaxation of an electron from a higher-energy orbital at the excited donor to the lower-lying LUMO localized at the acceptor site.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that two kinds of hydrogen‐bonded dimer arrays, ADAD–DADA (A=acceptor, D=donor) dimers (minor) and AADD–DDAA dimers (major), can coexist in Meijer's 2‐ureido‐4[1 H ]‐pyrimidinone motif, owing to the homodimerization of tautomeric monomers . However, the ADAD tautomer and ADAD–DADA dimeric structure are effectively inhibited by the degenerate prototropy effect in the modified molecule . This was supported by the 1 H NMR and X‐ray diffraction data.…”
Section: Figurementioning
confidence: 84%